Factors determining the outcome of paediatric exotropia surgery - Lai, Ivan Yoon Kit; Ting, Siew Leng; Cheah, Whye Lian; Ramasamy, Sunder; Jamalia, Binti Rahmat (Malaysian Medical Association, 2019)
Objective: To determine the socio-demographic and clinical profile of exotropia surgery outcomes amongst paediatric patients. Methods: This is a descriptive, retrospective, clinical study of surgeries performed between 2014 and 2016 at the Sarawak Heart Centre, Malaysia. Medical records of patients with primary and secondary exotropia were reviewed. The following factors that affected the surgical outcomes were collected: onset age of squint, age at the time of surgery, the interval between diagnosis and surgery, the type of exotropia, visual acuity, presence of amblyopia, previous patching, anisometropia, refractive error, type of surgery, preoperative and postoperative deviation, pre-existing ocular comorbidity and systemic illness. Result: A total of 15 patients were studied with more than two thirds being females. Seven patients had primary exotropia while eight patients had secondary exotropia. Average interval between diagnosis and surgery was 1.3 years (±0.82) for primary exotropia and 1.2 years (±0.84) for secondary exotropia. Average pre-operative angle for primary exotropia was 50.57PD (±10.83) whereas secondary exotropia was 39.38PD (±8.63). Seven patients had successful surgical outcomes of within 10 prism dioptres, five for primary exotropia and two for secondary exotropia. The response to surgery was 3.0PD/mm (±0.59) for primary exotropia and 2.2PD/mm (±0.74) for secondary exotropia.